Islamic Jurisprudence and Ethics: A Study based on al-Ghazali’s ‘Iha’y ‘ūlūm ḍḍin - Raki, Abdelhamid; Agli, Mustapha; Laklimi, Ahmed; Choubed, Noreddine (Journal of Ecohumanism, 2024)
Our purpose in this paper is to show the interrelation between Islamic jurisprudence as a science that contains high values and ethics. The impetus of this research is the two causes, the first is the absence of this relation in most of the Islamic literature, especially in the history of jurisprudence, and the second is the direct elimination of the Islamic thought in the ethical scope by the Western researchers in their contemporary studies. The author of this paper based on the heritage of al-Ghazali (d. 505 AH- 1111 CE), especially in his masterpiece ‘Iha’y ‘ūlūm ḍḍin.